2016
DOI: 10.3168/jds.2015-10428
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating mixed rations and formulated grain mixes into the diet of grazing cows: Effects on milk composition and coagulation properties, and the yield and quality of Cheddar cheese

Abstract: Effects of different strategies for feeding supplements to grazing dairy cows on the composition and coagulation properties of milk and the subsequent yield and quality of Cheddar cheese were measured. The experiment used milk from 72 Holstein-Friesian cows, averaging 45d in milk, fed according to 1 of 3 feeding strategies: (1) cows grazed a restricted allowance of perennial ryegrass pasture [approximately 14kg of dry matter (DM)/cow per day, to ground level] supplemented with milled wheat grain fed in the mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…All compositional parameters and pH at 1 d were unaffected by feeding system in ML, LL, or ML + LL. The absence of an effect of feeding system on cheese composition is consistent with the results of previous studies showing little effect of plane of cow nutrition or breed on LMPS Mozzarella (Guinee et al, 1998) or Cheddar cheese (Auldist et al, 2004(Auldist et al, , 2016O'Callaghan et al, 2017). Lactation period had a significant effect on composition, with cheeses from LL milk having significantly higher contents of moisture, salt-in-moisture, and moisture-in-nonfat substances, and lower contents of protein, fat and fat-in-DM.…”
Section: Cheese Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…All compositional parameters and pH at 1 d were unaffected by feeding system in ML, LL, or ML + LL. The absence of an effect of feeding system on cheese composition is consistent with the results of previous studies showing little effect of plane of cow nutrition or breed on LMPS Mozzarella (Guinee et al, 1998) or Cheddar cheese (Auldist et al, 2004(Auldist et al, , 2016O'Callaghan et al, 2017). Lactation period had a significant effect on composition, with cheeses from LL milk having significantly higher contents of moisture, salt-in-moisture, and moisture-in-nonfat substances, and lower contents of protein, fat and fat-in-DM.…”
Section: Cheese Compositionsupporting
confidence: 89%
“…As for protein, the effects of altering fat content depend on the degree of fat reduction and manufacturing procedure (Rudan et al, 1999;Fenelon and Guinee, 2000;Henneberry et al, 2015Henneberry et al, , 2016Mc-Carthy et al, 2016). Auldist et al (2016) investigated the effect of varying the type and quantity of supplement (wheat grain, corn grain, canola meal, alfalfa hay) to cows grazed on perennial ryegrass. Altering the diet affected milk fat content, fatty acid profile, and cheese yield, but not milk protein concentration, protein profile, or rennet gelation properties.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Devold et al [259] demonstrated cows on a diet supplemented with ecologically rolled barley had significantly larger micelle size than a group of cows supplemented with commercial concentrates, signifying the association feeding has with casein micelle size. Results from a study by Auldist et al [260] contrastingly found that altering the quantity of supplemental feed to grazing cows had no significant effect on the average casein micelle size. In Scotland, milk from the summer months produced casein with smaller micellar size than that from winter [261].…”
Section: Casein Micelle Sizementioning
confidence: 95%
“…Provision of corn grain and canola meal in a partial mixed ration or formulated grain mix to grazing cows receiving standard parlor meal and alfalfa hay was observed to have a beneficial effect on Cheddar cheese yield by Auldist, Greenwood, et al. (2016), with no changes to coagulation properties, cheese composition, or sensory acceptability.…”
Section: Impact Of Milk Composition On Dairy Product Functionalitymentioning
confidence: 95%